The Role of Recrystallization in Spontaneous Grain Refinement of Rapidly Solidified Ni3Ge - Haque, Nafisul; Cochrane, Robert F.; Mullis, Andrew M. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2017)
The congruently melting intermetallic β-Ni 3 Ge has been subject to rapid solidification via drop-tube processing. Droplets spanning the size range 75 to 53 μ m, with corresponding cooling rates of 23,000 to 42,000 K s −1 , have been found to undergo spontaneous grain refinement by recrystallization and recovery. Outside of this relatively narrow size range, the primary solidification morphology is retained, either dendritic for larger particles or dendritic seaweed for smaller particles.